2019
DOI: 10.1002/mp.13659
|View full text |Cite
|
Sign up to set email alerts
|

Automatic quantitative analysis of pulmonary vascular morphology in CT images

Abstract: PurposeVascular remodeling is a significant pathological feature of various pulmonary diseases, which may be assessed by quantitative computed tomography (CT) imaging. The purpose of this study was therefore to develop and validate an automatic method for quantifying pulmonary vascular morphology in CT images.MethodsThe proposed method consists of pulmonary vessel extraction and quantification. For extracting pulmonary vessels, a graph‐cuts‐based method is proposed which considers appearance (CT intensity) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Comorbidities, affecting the health status of the patient and thereby possibly influencing the LVR selection, may also be detectable. For instance, due to the relatively high contrast between pulmonary parenchyma and pulmonary vessels, the vessels can be segmented out of the lung [85]. The segmented vessels could provide useful information on pulmonary hypertension [86,87], as pulmonary hypertension involves vascular remodelling [88,89].…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities, affecting the health status of the patient and thereby possibly influencing the LVR selection, may also be detectable. For instance, due to the relatively high contrast between pulmonary parenchyma and pulmonary vessels, the vessels can be segmented out of the lung [85]. The segmented vessels could provide useful information on pulmonary hypertension [86,87], as pulmonary hypertension involves vascular remodelling [88,89].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study, which found that CT-based pruning was associated with thickening of the walls of the small pulmonary vessels and a resulting loss in luminal cross- We are aware of only one other study to examine the relationship between volumetric CT measures of the pulmonary vasculature and histologic changes in the pulmonary arterioles, with the Rahaghi study being the other 11 . While not directly relevant to histologic changes, Zhai and colleagues also found that CT-based methods of quantifying pulmonary vascular morphology were able to accurately capture pulmonary vessels using a 3D-printed vascular phantom which included vessels as small as 0.2mm (200µm) in diameter 31 . Our study's strengths include a relatively large cohort size, which is one of the largest to investigate the correlations of radiographic and histologic pulmonary vascular morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of quantifying the volume of the compromised lung from a simple unenhanced chest CT performed upon admission resides in the fact that this method can identify minimal changes in voxel units that may not be visible to the unaided eye. Many studies have reported its use in research on interstitial lung diseases, pulmonary sarcoidosis, and pulmonary vascular diseases [17][18][19].…”
Section: Discussionmentioning
confidence: 99%